1994
DOI: 10.1002/pssb.2221830216
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure calculation of Mg, Si, P, S, and Cl impurities in aluminium

Abstract: A fully self-consistent calculation using the multiple scattering X, method is used to study the electronic structure, the relation between charge transfer and electronegativity, the bonding characteristics, and the alloying of Mg with Al. The present investigation indicates that the charge transfer from the host A1 atoms to the central impurity atom increases with the increase of electronegativity of impurity atoms. It is found that the bonding is metallic for AlLMg and for the othcr impurities considered it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Electronegativities being same for both Se and Te the amount of charge transfer is much different. This seems to suggest that electronegativity is not the only factor determining the amount of charge transfer between the host atoms and the impurity atoms [21]. The bonding characteristics of the impurities with the host Si atoms can be inferred from the total charge residing within the central impurity and the first neighbour Si atoms.…”
Section: Charge Transfer and Bonding Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electronegativities being same for both Se and Te the amount of charge transfer is much different. This seems to suggest that electronegativity is not the only factor determining the amount of charge transfer between the host atoms and the impurity atoms [21]. The bonding characteristics of the impurities with the host Si atoms can be inferred from the total charge residing within the central impurity and the first neighbour Si atoms.…”
Section: Charge Transfer and Bonding Characteristicsmentioning
confidence: 99%
“…It is a more realistic method of dealing with the spatially localized deep level problems [13]. Many authors have extensively used this method to investigate the electronic structure of impurities in semiconductors [16 to 19] and in metals [20,21]. Very recently the authors have reported [22] the results of their study on the electronic structure of chalcogen (S, Se and Te) impurities in Si using the above method, but without taking into account the effect due to local lattice relaxation.…”
Section: Introductionmentioning
confidence: 96%